FOOD AND FEEDING HABITS OF THE SPOTTED HERRING, HERKLOTSICHTHYS PUNCTATUS (RUPPELL) FROM THE ANDAMAN SEA - Marichamy, R (Indian Journal of Fisheries, 2011)
Clupeids being economically important food fishes in India, their food andfeeding habits have been investigated in detail by many workers. Special mentionmay be made of the investigations on Sardlnella longiceps (Hornell and Nayudu,1924; Nair, 1953; Dhulkhed, 1962), Sardinella gibbosa {JDey/anesan, 1932; Ganapatiand Rao 1957), Kowala coval (Na.it, 1951), Thrissocles mystax, (Venkataraman, 1956),Raconda russellina (Va.T^e&e, 1961) and Coilia feorneenjij (Varghese, 1961). However,practically no information is available on the food and feeding habits ofHerklotsichthys punctatus (Ruppel) a clupeid \^'hich is commercially important inthe waters around Andaman Islands. A detailed study on the biology ofH. punctatus was undertaken during the years 1965-67 and the present accountrelates to the food and feeding habits of this species. .